Understanding Weed Biology to manage wheat field efficiently - Singh, Anil Kumar (Indian Farming, 2017)
Phalaris minor is a dominant weed in the areas where rice-wheat is a major cropping sequence. By virtue of its phonological advantage and its immense potential to survive under any adversity with the help of dormancy mechanisms, altogether posing greater challenge for its efficient scientific management. Before the situation slips out of hand, effective measure should be taken to nab this problem. An integrated approach involving weed biology, modified agronomic and herbicide practices is essential for efficient weed management and successful wheat production in the region There is immense need of a more vital extension approach, which can create the awareness among the farmers about this nasty problem and their management, so that the farmers, and all research and extension activities, can be benefited well in time.